Biopsy‐proven acute cellular rejection as an efficacy endpoint of randomized trials in liver transplantation: a systematic review and critical appraisal. (29th January 2016) - Rodríguez‐Perálvarez, Manuel; Rico‐Juri, Jose M.; Tsochatzis, Emmanuel; Burra, Patrizia; De la Mata, Manuel; Lerut, Jan
Summary: Biopsy‐proven acute cellular rejection (ACR) is the primary efficacy endpoint in most randomized trials evaluating immunosuppression in liver transplantation. However, ACR is not a major cause of graft loss, and a certain grade of immune activation may be even beneficial for long‐term graft acceptance. Validated criteria to select candidates for liver biopsy are lacking, and routine clinical practice relies on liver tests, which are inaccurate markers of ACR. Indeed, both the agreement among clinicians to select candidates for liver biopsy and the correlation between the clinical suspicion of ACR and histological findings are poor. In randomized trials evaluating immunosuppression protocols, this concern grows exponentially due to the open‐label and multicenter nature of most studies. Therefore, biopsy‐proven ACR is a suboptimal efficacy endpoint given its limited impact on prognosis and the heterogeneous diagnosis, which may increase the risk of bias. Chronic rejection and/or graft loss would be more appropriate endpoints, but would certainly require larger studies with prolonged surveillances. An objective method to select candidates for liver biopsy is therefore urgently needed, and only severe episodes of histological ACR should be considered as potentially harmful. Emerging surrogate markers of ACR and antibody‐mediated rejection require further investigation to determine their clinical role.